An efficient computational approach for control of nonlinear transient responses of smart piezoelectric composite plates. (November 2015) - Phung-Van, P.; Nguyen, Lieu B.; Tran, Loc V.; Dinh, T.D.; Thai, Chien H.; Bordas, S.P.A.; Abdel-Wahab, M.; Nguyen-Xuan, H.
Abstract: An efficient computational approach based on a generalized unconstrained approach in conjunction with isogeometric analysis (IGA) are proposed for dynamic control of smart piezoelectric composite plates. In composite plates, the mechanical displacement field is approximated according to the proposal model using isogeometric elements and the nonlinear transient formulation for plates is formed in the total Lagrange approach based on the von Kármán strains and solved by Newmark time integration. Through the thickness of each piezoelectric layer, the electric potential is assumed linearly. For active control of the piezoelectric composite plates, a close-loop system is used. An optimization procedure using genetic algorithm (GA) is considered to search optimal design for actuator input voltages. Various numerical examples are investigated to show high accuracy and reliability of the proposed method. Highlights: An efficient computational approach following a generalized unconstrained theory and isogeometric analysis (IGA) is proposed. It is then used for active control of nonlinear transient responses of smart piezoelectric composite plates. A procedure to search optimal design for actuator input voltages in piezoelectric plates is investigated. The numerical results demonstrate high efficiency of the present method.